Modern Judaism : an Oxford guide - De Lange, N. R. M. (Nicholas Robert Michael), 1944-; Freud-Kandel, Miri. (Oxford ; New York : Oxford University Press, 2005)
"A multi-disciplinary, multi-authored guide to Jewish life and thought. This book covers the major areas of thought in Jewish Studies, including considerations of religious differences, sociological, philosophical, and gender issues, geographical diversity, inter-faith relations, and the impact of the Shoah (the Holocaust) and the modern state of Israel"--Provided by publisher.
Demographic issues / Uzi Rebhun -- Enlightenment and emancipation / Lois C. Dubin -- Persecution / Robert Jan van Pelt -- A national home / Emanuele Ottolenghi -- Post-Zionism / Emanuele Ottolenghi -- Modernist movements / Miri Freud-Kandel -- Traditionalist strands / Eliezer Don-Yehiya -- Humanistic and secular Judaisms / Yaakov Malkin -- Jewish renewal / George R. Wilkes -- American Jewry / Chaim I. Waxman -- Israeli Jewry / Eran Kaplan -- French Jewry / Paula E. Hyman -- British Jewry / Miri Freud-Kandel -- Jewry in the former Soviet Union / John Klier -- Social issues: survey / Harvey E. Goldberg -- Jewish identities / Ezra Kopelowitz -- Fundamentalism / Nurit Stadler -- Prayer and worship / Ruth Langer -- he authority of texts / Nicholas de Lange -- The future of Jewish practice / Jeremy Wanderer -- Theological issues: survey / Norbert M. Samuelson -- Revelation / David Novak -- Covenant / Peter Ochs -- Philosophical issues: survey / Kenneth Seeskin -- The problems of evil / Daniel Rynhold -- Jewish ethics in a modern world / Michael Zank -- Halakhic issues: survey / Jonathan Cohen -- Halakhah and Israel / Daniel Sinclair -- Contemporary issues in halakhah / Steven H. Resnicoff -- Gender issues: survey / Susannah Heschel -- The changing role of the woman / Judith R. Baskin -- Sexuality / Mark Solomon -- As others see Jews / Elliot Horowitz -- Jewish-Christian relations / Margie Tolstoy -- Jewish-Muslim relations / Reuven Firestone.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Judaism; Jews; Judaism; Jews; Judaïsme.; Juifs; RELIGION -- Judaism -- History; Jews; Judaism; Jodendom; Electronic books